Ilościowe charakterystyki jednolitego rynku ubezpieczeniowego Wspólnoty Europejskiej oraz podstawowe czynniki jego zmian - Lemkowska, Malwina (Quantitative Characteristics of European Union Single Market and the Main Factors of Its Change, 2008)
The European Union Insurance Single Market constantly changes. The volume of gross premium written is growing. The rate of growth is higher in new member states but the volume of premium written each year is significantly higher in 15 old member countries. This means that the potential of "old Union" is still very high and insurers have great possibility to achieve gains by performing there. The connection between the rate of growth of premium written per capita, GDP per capita and the volume of GDP per capita is very interesting. In the countries with low volume of GDP per capita, both indicators grew in most cases and the growth rate of premium per capita was significantly higher. The opposite situation was observed in countries with high level of GDP per capita. There are many law, economic and social factors changing insurance market. The main are: deregulation, liberalization, globalization, concentration of risk, new technologies and as a consequence of these indicated - the evolution of insurer's structures, especially tendency to concentration on core business through outsourcing and rebuilding product's offer. All these factors should be recognized and respected by insurers who want to achieve gains in the European Market.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1197, s. 205-212